Magnitude and direction of elbow torque asymmetries in manual wheelchair users - Biduski, Grazieli Maria; Knihs, Débora Aparecida; Nery de Oliveira, Silas; Hoinaski, Laís Peixoto; Rossato, Mateus; Freitas, Cíntia De La Rocha (Frontiers in Sports and Active Living, 2023)
The aims of the present study were to investigate the magnitude and direction of the elbow torque asymmetries in manual wheelchair users, and to verify the agreement levels of the asymmetry's direction between different velocities and contraction modes in the isokinetic test. Fourteen manual wheelchair users (4 women, 10 men) composed the sample. The elbow flexors and extensors peak of torque were measured on dominant and non-dominant limbs, through a set of concentric/eccentric contractions, at speeds of 60°s -1 and 180°s -1 . Asymmetries were calculated by a specific equation, and the level of agreement of the asymmetry's direction were calculated through Kappa coefficient. The main results showed large variability in the asymmetries magnitude, ranging from -73.1% (ND) to 59.9% (D) between participants. The agreement levels of the elbow's flexors and extensors between the different contraction modes were great (k = 0.71 to 0.85) for most of the velocities (except for flexors 60°s -1 (k = 0.29)), but only slight to fair (k = 0.16 to 0.31) for most of the contraction modes when comparing between velocities (except for flexors eccentric (k = 0.71)). In conclusion, elbow torque asymmetries are highly variable between subjects in terms of magnitude. In addition, in general, the limb favored by the asymmetry is the same when comparing between velocities, but not when comparing between contraction modes.